A framework for analyzing in-band crosstalk accumulation in ROADM-based optical networks - Chentsho, P. (2022)
Reconfigurable optical add-drop multiplexers (ROADMs) are central pieces in building transparent optical transport networks. However, due to physical limitations, these devices can be a source of in-band crosstalk, which affects the quality of the lightpaths routed and the network performance. Hence, to efficiently design optical networks it is important to study how this impairment is generated and to understand its dependency on relevant network parameters, such as the number of wavelengths used and the node degree. In this paper, we propose a framework to analyze the in-band crosstalk accumulation inside of ROADM-based networks. The framework computes the number of accumulated crosstalk terms in each link of a lightpath considering different physical topologies, as well as different routing and wavelength assignment strategies. An empirical formula is also derived for computing the maximum number of accumulated crosstalk terms as a function of the network parameters. We observe that in the majority of the studied cases, there is a complete agreement between the results of the proposed framework and the empirical formula.